2008
DOI: 10.1016/j.brainres.2007.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic alcohol consumption on brain damage following transient focal ischemia

Abstract: Chronic alcohol consumption impairs cerebral vasoreactivity, and thus, may result in an increase in ischemic brain damage. The goal of this study is to examine the influence of chronic alcohol consumption on transient focal ischemia-induced brain damage. Sprague-Dawley rats were divided into two groups, a control group and an alcohol group. Eight weeks after being fed a liquid diet with or without alcohol, responses of parietal pial arterioles to systemic hypoxia and hypercapnia were measured using a cranial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…The rat was mounted in the prone position on a dual small animal stereotaxic instrument (Reworld Instruments, Shanghai, China). After cranial midline incision, a 1-mm burr hole was made with microdrill on the right side, 1-mm-posterior and 5-mm-lateral to bregma (Sun et al 2008), and the rat was placed in the supine position. A laser Doppler probe was placed on the burr hole under the rat skull, nearly contacting the dura mater and avoiding large vessels, and measured the parietal cortical perfusion in the middle cerebral artery territory.…”
Section: Regional Cerebral Blood Flow Measurementmentioning
confidence: 99%
“…The rat was mounted in the prone position on a dual small animal stereotaxic instrument (Reworld Instruments, Shanghai, China). After cranial midline incision, a 1-mm burr hole was made with microdrill on the right side, 1-mm-posterior and 5-mm-lateral to bregma (Sun et al 2008), and the rat was placed in the supine position. A laser Doppler probe was placed on the burr hole under the rat skull, nearly contacting the dura mater and avoiding large vessels, and measured the parietal cortical perfusion in the middle cerebral artery territory.…”
Section: Regional Cerebral Blood Flow Measurementmentioning
confidence: 99%
“…After a cranial midline incision, a 1-mm burr hole was made with a microdrill at both sides, 2-mm-posterior and 5-mm-lateral to the bregma 24) . The rat was then placed in the supine position.…”
Section: Regional Cerebral Blood Flowmentioning
confidence: 99%
“…Scoring for rats was performed blindly with a 24-point scale modified from Garcia's neurological scoring system (Sun et al, 2008). Sensorimotor testing was graded on a scale of 0 to 3 each on spontaneous activity, symmetry of movement, response to vibrissae touch, floor walking, beam walking, symmetry of forelimbs, climbing wall of wire cage, reaction to touch on either side of trunk.…”
Section: Neurological Evaluationmentioning
confidence: 99%
“…Recently, we found that chronic alcohol consumption exacerbates transient focal ischemia-induced brain injury (Sun et al, 2008).…”
mentioning
confidence: 99%